Advanced topics in forensic DNA typing : interpretation - Butler, John M. (John Marshall), 1969- (Academic Press, 2015)
The first edition of Forensic DNA Typing, published in 2001, by John Butler quickly established itself as the gold-standard reference for the field. Over the next ten years, the vast amount of new information uncovered has resulted in this new volume, Advanced Topics in Forensic DNA Typing: Interpretation. This book builds upon the previous two editions of Forensic DNA Typing books, but with a focus on mixture interpretation and statistical analysis and is a companion to the bestselling Advanced Topics in Forensic DNA Typing: Methodology, published in September 2011. Provides forensic DNA ana.